Research Perspectives in Coroplastic Studies: The Distribution, Trade, Diffusion, and Market Value of Greek Figurative Terracottas - Jaimee P. Uhlenbrock (Les Carnets de l’ACoSt)
The hundreds of thousands of Greek figurative terracottas that have been brought to light at sites around the Mediterranean and Black Sea from the late seventh to the first century B.C.E. provide excellent evidence for trade and diffusion, on both a local and international level. We know that at certain terracotta-producing centers figurative terracottas were produced far in excess of local needs, suggesting that they must have been conceived as exportable items driven by a market demand within long-distance trading networks. The ability to recognize the products of specific coroplastic manufacturing centers through clay analysis has facilitated the recognition of the extent to which figurative terracottas and their molds were marketed abroad. Moreover, an attentive examination of mold series or contextual evidence can offer clues to modes of diffusion and the consequent influence that this diffusion may have exercised on a distant terracotta-producing center. Finally, the nature and extent of that influence, as well as certain technical features that accompanied it, may shed some light on the market value, or worth, that may have been assigned to certain of these figurative terracottas at given periods.